2016
DOI: 10.2337/dc15-2782
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Variability in a 26-Week Randomized Comparison of Mealtime Treatment With Rapid-Acting Insulin Versus GLP-1 Agonist in Participants With Type 2 Diabetes at High Cardiovascular Risk

Abstract: OBJECTIVEA1C is associated with diabetes complications but does not reflect glycemic variability (GV), which may worsen outcomes by inducing inflammation, oxidative stress, and cardiac arrhythmias. We tested whether a glucagon-like peptide 1 agonist-based regimen can reduce GV and cardiometabolic risk markers while maintaining similar A1C levels in people with insulin-requiring type 2 diabetes and high cardiovascular risk. RESEARCH DESIGN AND METHODSAfter run-in on metformin and basal-bolus insulin (BBI), 102 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…The FLAT‐SUGAR (Fluctuation Reduction With Insulin and GLP‐1 Added Together) trial recently examined the effects of twice‐daily exenatide + insulin glargine + metformin versus rapid‐acting insulin + insulin glargine + metformin on glycaemic variability measured using CGM in participants with type 2 diabetes 24. Twice‐daily exenatide significantly reduced the glucose CV and MAGE compared with prandial insulin, while HbA1c was similar in both groups at study end.…”
Section: Discussionmentioning
confidence: 99%
“…The FLAT‐SUGAR (Fluctuation Reduction With Insulin and GLP‐1 Added Together) trial recently examined the effects of twice‐daily exenatide + insulin glargine + metformin versus rapid‐acting insulin + insulin glargine + metformin on glycaemic variability measured using CGM in participants with type 2 diabetes 24. Twice‐daily exenatide significantly reduced the glucose CV and MAGE compared with prandial insulin, while HbA1c was similar in both groups at study end.…”
Section: Discussionmentioning
confidence: 99%
“…FLAT-SUGAR was a 26-week study comparing the effects on glycemic fluctuations (measured using CGM) of the GLP-1RA exenatide twice daily (BID) or rapid-acting insulin as prandial add-on therapy to insulin glargine plus metformin in patients with T2D ( n = 102). 49 While exenatide BID and prandial insulin both target postprandial glucose concentrations, the insulinogenic effects of exenatide BID are glucose dependent, in contrast to insulin ( Table 1 ). After 26 weeks of treatment, HbA 1c levels were comparable in the exenatide BID and rapid-acting insulin groups (7.1% and 7.2%, respectively).…”
Section: Cgm To Evaluate Effectiveness Of Treatments On Glycemic Flucmentioning
confidence: 99%
“…Glycemic variability refers to swings in blood glucose levels (28) and is associated with increased oxidative stress (29). The initial result of proof-of-concept FLAT-SUGAR trial (Fluctuation Reduction With Insulin and GLP-1 Added Together) showed that at week 26 the %CV, MAGE, weight, alanine transaminase, and serum amyloid were significantly higher in basal-bolus insulin-treated group versus the basal insulin plus exenatide group, but there was no significant difference between groups regarding glycemic control (HbA1c), hypoglycemic episodes, or other biomarkers (interleukin-6, high-sensitivity C-reactive protein, albuminuria or urinary isoprostanes) (30). It is difficult to perform a quantitative measurement of glycemic variability since it is dependent on amplitude and duration of the fluctuations of glycemic values (31).…”
Section: Discussionmentioning
confidence: 99%